Invisible and precarious work? Professionalizing the care sector to foster the integration of women in vulnerable situations - ED-Douadi , Safae; M’Barki , Rayyane (Revue Internationale du Chercheur, 2026)
In Morocco, precariousness and poverty among women often compel them to enter the care sector, which remains largely informal and undervalued. While this sector can provide an initial source of income, it rarely enables long- term socio - economic integration. This article investigates the structural and institutional factors that hinder or support the professionalisation of the care economy and its potential as a vector for women’s empowerment. Drawing on a qualitative fie ld study involving 13 semi - structured interviews conducted in May 2025 with care workers and representatives of women’s rights associations, the analysis highlights key levers such as legal recognition, access to training, social value attribution, and coo rdinated institutional support. The findings contribute to current debates on gender, informality of women’s work, and social justice, emphasizing the need for a more structured and rights - based approach to care work in Morocco.